Strategi Sumber Daya Manusia (SDM) dalam Pemasaran Jasa Pendidikan - Dedi Abu Samsudin; Anis Zohriah; Abdul Mu'in (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Education is a valuable investment for the future, and marketing educational services is an important aspect in making educational institutions high quality. This research was conducted to determine aspects of human resources in marketing educational services. This research uses qualitative methods and the data collection technique used in this research is library research, namely the research object used by searching for and collecting data or literary information in the form of books, journals, magazines, reports, and the others. The results of this research show that marketing educational services is very important in improving the quality of education. Product, price, place, promotion, people, physical evidence, process are important elements in marketing educational services. Meanwhile, in practice there are several marketing strategies for educational services, namely; market identification, market segmentation, product differentiation, and school services.